2015
DOI: 10.1007/s10508-015-0597-y
|View full text |Cite
|
Sign up to set email alerts
|

Binge Drinking in Young Adulthood: The Influence of Age at First Intercourse and Rate of Sex Partner Accumulation

Abstract: There has been growing attention to the influence of youths’ sexual experiences on alcohol use and other health-risk behaviors. Yet, because of the cross-sectional nature of many studies, as well as the likelihood of alcohol use and sexual behaviors to co-occur, the question of whether initiation of sexual activity tends to precede engagement in other behaviors, like binge drinking, remains largely unanswered. Using data from 4,726 respondents who participated in Waves I though IV of the National Longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
(77 reference statements)
1
5
0
1
Order By: Relevance
“…Under the context that all the participants in this study were regular users of alcohol and tobacco, the early sexual initiators still reported more regular binge drinking than the nonearly sexual initiators. This is consistent with previous studies showing early sexual initiators to have increased risk of binge drinking [ 57 , 58 ]. Furthermore, the early sexual initiators reported more lifetime illicit drug use, in which ketamine was the most commonly used drug, and more preceding-sex use of illicit drugs than the nonearly sexual initiators.…”
Section: Discussionsupporting
confidence: 93%
“…Under the context that all the participants in this study were regular users of alcohol and tobacco, the early sexual initiators still reported more regular binge drinking than the nonearly sexual initiators. This is consistent with previous studies showing early sexual initiators to have increased risk of binge drinking [ 57 , 58 ]. Furthermore, the early sexual initiators reported more lifetime illicit drug use, in which ketamine was the most commonly used drug, and more preceding-sex use of illicit drugs than the nonearly sexual initiators.…”
Section: Discussionsupporting
confidence: 93%
“…Possibly, the prevention program left girls better equipped to moderate their drinking. Differences in binge drinking rates are notable because as girls enter early adulthood, their associated risks of excessive alcohol use include: unprotected sex, multiple sex partners, unintended pregnancies, sexually transmitted diseases, and sexual assault (Haas et al 2016; Holway et al 2017). The ability to minimize binge drinking, therefore, confers numerous benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The standard social science approach to the study of sex partner accumulation is plentiful in its research output but also largely atheoretical, focusing on various risk and protective factors among children and adolescents, such as poverty, religion, peers, and parent-child relationships (e.g., Coley et al, 2013;Halpern et al, 2000;Hardy et al, 2019;Holway et al, 2017;Hughes et al, 2017;Kan et al, 2010;Kogan et al, 2017, Warner, 2018. To briefly summarize, this study finds that youth from abusive and economically unstable homes, who are not religious and not academically engaged, who use drugs and alcohol and associate with risky peer groups, tend to have sex earlier and with more partners than their conventionally situated peers.…”
Section: Prior Theorizing and Researchmentioning
confidence: 99%